Diversity, Identity And Cultural Expression: A Perspective From The Local Cultural Wisdom Of The Sultanate Of Buton - Malihu, La (Universitas Negeri Makassar, 2024)
This study aims to trace the philosophical expressions that developed in the Buton Sultanate. Using a historical method by reviewing the archives documents and other relevant books and articles. The results of the study show that there are a number of philosophical expressions that are filled with unity and the spirit of self defense for survival. This has proven to be an integrative factor that unites society in everyday life so that the Buton Sultanate was able to maintain its existence from the threat of various external forces for around 600 years.Keywords: Diversity, Cultural Wisdom, Sultanate of Buton